ORNAMENTS IN THE TREATY VERSUCH EINER ANWEISUNG DIE FLÖTE TRAVERSIÈRE ZU SPIELEN (1752) FROM JOHANN JOACHIM QUANTZ - Ignác Csaba FILIP (Studia Universitatis Babeş-Bolyai. Musica)
The application of the performing principles ornaments described by Quantz is valid for all the performers who wish to represent the baroque music according to its rules and to the rules of the epoch. These rules can be applied not only with modern instruments but also in case of baroque instruments and the majority of the principles of ornamentations can be found throughout the history of music till nowadays.